Radiographic evaluation of periapical status and coronal restoration in endodontically treated teeth: a pilot study - GENÇOĞLU, NİMET; GÖKYAR, MERVE (My University, 2022)
Aim: The aim of this study is to examine the relationship between the type and quality of coronal restoration and their periapical status in endodontically treated teeth. Materials and Methods: In this retrospective study, CBCT and panoramic X-ray images which were taken in 2020-2021, in Marmara University Faculty of Dentistry, Department of Oral and Maxillofacial Radiology were investigated. In this study, the patients who were 18-70 years old and had at least one root canal treatmente were chosen. A total of 200 patients with 4327 teeth were examined. Among these teeth, 452 teeth had root canal filling. The quality and type of coronal restoration and the periapical health status of these teeth were examined.For evaluating periapical health status, periapical index scoring (KIBTPAI) was used. Results: It was found that 10.4 % of all teeth had root canal treatment. In addition, the prevalence of apical periodontitis was found to be %58.4 in endodontically treated teeth. 61.2% of these teeth had inadequate coronal restoration. Meanwhile, 66.4% of teeth with insufficient coronal restoration had periapical lesions. Conclusion: According to the findings of this study, the incidence of apical periodontitis was found to be higher in teeth with insufficient coronal restoration.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); apical periodontitis; endodontically treated teeth; CBCT images; coronal restoration; Periapical status